2023
DOI: 10.1002/cctc.202201394
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Magnesium‐Mediated Formal Hydroformylation of Alkynes and Alkenes

Abstract: Alkynes and alkenes are routinely converted to corresponding synthetically versatile aldehydes using rhodium-catalyzed hydroformylation. However, rhodium is rare, precious, costly, and depleting at a considerably high rate. Reported here is ironcatalyzed, magnesium-mediated, formal hydroformylation of alkynes and alkenes in the absence of syngas. Readily available FeCl 2 in the presence of alkyl magnesium halide, and dimethyl formamide, catalyzes hydroformylation of various alkynes and selectively produces α,β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The electrochemical CO Oxid on the surface of Pt-group catalysts in or out of alcohol fuel cells is undeniably a complex process, so it is essential to decipher its pathway and mechanisms to improve the catalytic performance of such fuel cells and reduce the CO-poisonous. [22] There are various proposed processes for the CO Oxid process on Pt-group catalysts, but mainly four mechanisms are the most acceptable, including the ligand effect, electronic effect, bi-functional effect, and hydrogen spillover effect, [6] which all start with CO adsorption, followed by diffusion, oxidation at Pt-group active sites, and finally, CO 2desorption (Figure 2a). In the ligand effect, the metal interacts with CO molecules, decreasing the binding energy between CO and the Pt surface and thus easing the CO Oxid .…”
Section: Co Oxidation Processmentioning
confidence: 99%
See 3 more Smart Citations
“…The electrochemical CO Oxid on the surface of Pt-group catalysts in or out of alcohol fuel cells is undeniably a complex process, so it is essential to decipher its pathway and mechanisms to improve the catalytic performance of such fuel cells and reduce the CO-poisonous. [22] There are various proposed processes for the CO Oxid process on Pt-group catalysts, but mainly four mechanisms are the most acceptable, including the ligand effect, electronic effect, bi-functional effect, and hydrogen spillover effect, [6] which all start with CO adsorption, followed by diffusion, oxidation at Pt-group active sites, and finally, CO 2desorption (Figure 2a). In the ligand effect, the metal interacts with CO molecules, decreasing the binding energy between CO and the Pt surface and thus easing the CO Oxid .…”
Section: Co Oxidation Processmentioning
confidence: 99%
“…Meanwhile, in the bifunctional effect, the delocalized d-orbital electrons on the metal surface induce the electron transfer to the Pt-group. [6,23] In the hydrogen spillover, a hydrogen atom is dissociated from the Pt-group surface and transferred to the metal sites, creating an interaction of COÀ Mo bond, whereas the metalÀ H interaction decreases the bond between CO and metal, resulting in facilitating the CO oxidation on the Pt surface. Various studies reported that Pt-based electrocatalysts with a uniform dispersion of Pt tend to show a stronger spill effect.…”
Section: Co Oxidation Processmentioning
confidence: 99%
See 2 more Smart Citations
“…We have been investigating the reactivity of various iron complexes in catalysis. [19,20,21,22] In a recent work, we proposed iron dihydride (Scheme 1, A) as an active species for hydroformylation. [23] However, the proposed species A is highly unstable.…”
Section: Catalyst Synthesismentioning
confidence: 99%